2016
DOI: 10.1038/onc.2016.17
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule-associated protein 4 is an important regulator of cell invasion/migration and a potential therapeutic target in esophageal squamous cell carcinoma

Abstract: Cell invasion and migration significantly contribute to tumor metastasis. Microtubule-associated protein 4 (MAP4) protein is one member of microtubule-associate proteins family. It is responsible for stabilization of microtubules by modulation of microtubule dynamics. However, there is little information about the involvement of MAP4 in human cancer. Here we show that MAP4 serves as a regulator of invasion and migration in esophageal squamous cancer cells. By activating the ERK-c-Jun-vascular endothelial growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
33
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 36 publications
8
33
1
Order By: Relevance
“…In addition, in the present study, low MAP4 expression was significantly associated with lower grade ( χ 2  = 22.933, df  = 2, P  < 0.001) which has also been observed in bladder cancer ( n  = 34) (Ou et al 2014). Although a higher level of MAP4 mRNA was found in non-small cell lung carcinomas when compared to normal lung tissues (Cucchiarelli et al 2008) and MAP4 expression was associated with shorter survival of the esophageal squamous cell carcinoma patients ( n  = 364) (Jiang et al 2016), no significant association was detected in the present study between MAP4 expression and overall survival in either the whole cohort or any of the subgroups tested.…”
Section: Discussioncontrasting
confidence: 66%
“…In addition, in the present study, low MAP4 expression was significantly associated with lower grade ( χ 2  = 22.933, df  = 2, P  < 0.001) which has also been observed in bladder cancer ( n  = 34) (Ou et al 2014). Although a higher level of MAP4 mRNA was found in non-small cell lung carcinomas when compared to normal lung tissues (Cucchiarelli et al 2008) and MAP4 expression was associated with shorter survival of the esophageal squamous cell carcinoma patients ( n  = 364) (Jiang et al 2016), no significant association was detected in the present study between MAP4 expression and overall survival in either the whole cohort or any of the subgroups tested.…”
Section: Discussioncontrasting
confidence: 66%
“…Judah Folkman verificated that tumor growth is dependent on the angiogenesis.He found that the diffuse substances secreted by the tumor can stimulate the proliferation of endothelial cells, and then form new blood vessels, and the tumor must form new blood vessels to provide nutrients after growing for more than a few millimeters [18]. It has been commal accepted that VEGF-A is the earliest discovered and most important pro-angiogenic factor [ 19 ].It has been demonstrated that VEGF overexpression potentiates the migratory and invasive ability of ESCC cells [20],which coincides with observations in other malignancies [21] and proliferation via activating cell signaling [23].Early studies have confirmed a positive correlation between IL-1β secretion in gastric cancer and NF-κB activation in tumors [24].Another study also reported that infection with H. pylori and IL-1β deficient mice does not activate gastric mucosal inflammation and NF-κB in epithelial cells [25].IL-1RA inhibits IL-1's tumor-promoting function by blocking IL-1 binding to its receptor [26].Our results show that overexpression of IL-1RA can reduce the phosphorylation level of PI3k in cells and further reduce the expression of NF-κB and it's phosphorylation, suggesting that IL-1RA may play a role through the PI3K/NF-κB signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…MAP4 (microtubule-associated protein 4), a major non-neuronal MAP, promotes microtubule assembly and counteracts destabilization of interphase microtubule catastrophe promotion. MAP4 interacts with cyclin B, which targets cell division cycle 2 (CDC2) kinase to microtubules [38,39]. [39].…”
Section: Discussionmentioning
confidence: 99%